2021
DOI: 10.1002/slct.202101314
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Hydrogenation of Phenol Catalyzed by Porous BN Supported Ni−Pd Catalysts

Abstract: Phenol, as a phenolic organic substance, is widely present in industrial wastewater and is an important organic pollutant. Porous boron nitride (p-BN) is an ideal material as catalyst support because it has a large specific surface area and a variety of pore structures. In this paper, a series of NiÀ Pd/p-BN catalysts were prepared by precipitation method. Meanwhile, the catalytic performance of the catalysts for the hydrogenation of phenol to cyclohexanol was systematical and comprehensive studied. Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The advantageous properties of porous boron nitride (BN) include its large specific surface area, abundant pore structure, superior thermal stability, and chemical inertness, , rendering it an attractive candidate for catalyst applications. , Recent research has explored utilizing BN and its modified forms as catalyst supports, demonstrating enhanced catalytic performance in various reactions. For example, porous BN nanofibers with a high specific surface area were employed as a support for CuCo nanoparticles, resulting in excellent dispersibility and stability of the composite catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The advantageous properties of porous boron nitride (BN) include its large specific surface area, abundant pore structure, superior thermal stability, and chemical inertness, , rendering it an attractive candidate for catalyst applications. , Recent research has explored utilizing BN and its modified forms as catalyst supports, demonstrating enhanced catalytic performance in various reactions. For example, porous BN nanofibers with a high specific surface area were employed as a support for CuCo nanoparticles, resulting in excellent dispersibility and stability of the composite catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. proposed 5Ni2Pd/p‐BN catalysts with porous boron nitride (p‐BN) as the support, which have large specific surface area, abundant active sites and excellent catalytic performance in phenol hydrogenation reactions [17] . Bi et al.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Zhang et al proposed 5Ni2Pd/ p-BN catalysts with porous boron nitride (p-BN) as the support, which have large specific surface area, abundant active sites and excellent catalytic performance in phenol hydrogenation reactions. [17] Bi et al developed that Co/BN catalysts had a high DMF selectivity (91.67 %), and the catalyst contained many BÀ O defects. Also, there was a strong interaction between the support BN and Co. [18] It has been shown that the doping of heteroatoms in h-BN materials can achieve the tuning of its structure and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, synthetic transformations requiring the activation of inert Csp 2 –H bonds are heavily dependent on the use of 4d- and 5d-based precious metal complexes. 6,7 However, given the scarcity and higher costs, it has become increasingly necessary to find alternatives incorporating earth-abundant elements from the 3d row.…”
Section: Introductionmentioning
confidence: 99%